Characterization of full-length CNBP expanded alleles in myotonic dystrophy type 2 patients by Cas9-mediated enrichment and nanopore sequencing - Alfano, Massimiliano; De Antoni, Luca; Centofanti, Federica; Visconti, Virginia Veronica; Maestri, Simone; Degli Esposti, Chiara; Massa, Roberto; D'Apice, Maria Rosaria; Novelli, Giuseppe; Delledonne, Massimo; Botta, Annalisa; Rossato, Marzia (eLife, 2022)
Myotonic dystrophy type 2 (DM2) is caused by CCTG repeat expansions in the CNBP gene, comprising 75 to >11,000 units and featuring extensive mosaicism, making it challenging to sequence fully expanded alleles. To overcome these limitations, we used PCR-free Cas9-mediated nanopore sequencing to characterize CNBP repeat expansions at the single-nucleotide level in nine DM2 patients. The length of normal and expanded alleles can be assessed precisely using this strategy, agreeing with traditional methods, and revealing the degree of mosaicism. We also sequenced an entire ~50 kbp expansion, which has not been achieved previously for DM2 or any other repeat-expansion disorders. Our approach precisely counted the repeats and identified the repeat pattern for both short interrupted and uninterrupted alleles. Interestingly, in the expanded alleles, only two DM2 samples featured the expected pure CCTG repeat pattern, while the other seven presented also TCTG blocks at the 3′ end, which have not been reported before in DM2 patients, but confirmed hereby with orthogonal methods. The demonstrated approach simultaneously determines repeat length, structure/motif, and the extent of somatic mosaicism, promising to improve the molecular diagnosis of DM2 and achieve more accurate genotype–phenotype correlations for the better stratification of DM2 patients in clinical trials.
Keywords: myotonic dystrophy type 2; CNBP gene; repeat expansion; Cas9-mediated enrichment; nanopore sequencing